2020
DOI: 10.1186/s12904-020-0530-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing preparedness for caregiving and death in family caregivers of patients with severe illness who are cared for at home – study protocol for a web-based intervention

Abstract: Background: Family caregivers of patients with severe illness and in need for a palliative care approach, face numerous challenges and report having insufficient preparedness for the caregiver role as well as a need for information and psychosocial support. Preparing to care for a severely ill family members also means becoming aware of death. Feelings of being prepared are associated with positive aspects and regarded protective against negative health consequences. Methods: The study adheres to the SPIRIT-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
0
16
0
7
Order By: Relevance
“…It is common for caregivers to request information from nurses. Nursing interventions are known to be effective, and information provided by nurses can have significant positive effects on family caregivers' feelings of readiness (Alvariza et al, 2020;Henriksson, Årestedt, et al, 2012;Holm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common for caregivers to request information from nurses. Nursing interventions are known to be effective, and information provided by nurses can have significant positive effects on family caregivers' feelings of readiness (Alvariza et al, 2020;Henriksson, Årestedt, et al, 2012;Holm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is common for caregivers to request information from nurses. Nursing interventions are known to be effective, and information provided by nurses can have significant positive effects on family caregivers' feelings of readiness (Alvariza et al, 2020; Henriksson, Årestedt, et al, 2012; Holm et al, 2016). Therefore, an updated model focusing on caregiver preparedness is required to predict the preparedness of family caregivers, anticipate their need for training activities and avoid negative caregiving effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study are also consistent with a study by Burgdorf et al ( 2019 :835), published in the JAMA Internal Medicine Journal , which revealed that more than three-quarters of caregivers are actively performing their caregiving roles without having undergone any training. A positive first impression is one of the factors that determine caregiver preparedness (Alvariza, Häger-Tibell & Holmet 2020 ). Caregiver preparedness is described as the perceived readiness of caregivers to undertake the caregiving role that includes the provision of physical and emotional support to those in need (Schumacher et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The informative texts will deepen and broaden the topics raised in the videos. As a part of the intervention, the website will also host an online peer-support discussion forum, which can be used by ICs to communicate with others in a similar situation (Alvariza et al, 2020).…”
Section: Phase II (Educational Material)mentioning
confidence: 99%